An Empirical Study on Family Related Issues in Health Sector - Kusuma, G.D.V.; Lakshmi, B. Vijaya; Kumar, B. Ravi (International Journal of Marketing Research Innovation, 2018)
This study "Women in Profession" is conducted on the basis of my observation and interaction with working women, especially professional women and the realization of the fact that they are passing through strenuous period of adjustment between work at home and profession. In order to get to the root of the problem it seemed necessary to study women in their social relations at work and to discover the processes whereby their social relations have changed over time. The present study is an attempt to depict the family related issues in selected hospitals.